Enacted support and golf-putting performance: The role of support type and support visibility - Moll, T.; Rees, T.; Freeman, P. (Psychology of Sport and Exercise, 2017)
Objectives: This study examined whether the impact of enacted support on performance differed across type (esteem and informational) and visibility (visible and invisible) of support. It further tested whether self-efficacy mediated the enacted support-performance relationship. Design: A one-factor (support manipulation) between subjects experiment. Method: A fellow novice golfer — in reality a confederate — was scripted to randomly provide one of five support manipulations (visible informational support, invisible informational support, visible esteem support, invisible esteem support, and no support) to participants (n=105). Immediately after, participants completed a self-efficacy measure and then performed a golf-putting task. Results: The results demonstrated that participants given visible esteem support significantly outperformed those given no support and those given invisible esteem support. Participants given invisible informational support significantly outperformed those given no support. Although non-significant, the observed mean difference and moderate effect size provided weak evidence that those in the invisible informational support condition may have performed at a higher level than those in the visible informational support condition. There was no evidence that self-efficacy could explain any of these effects. Conclusion: The results suggest that enacted support can benefit novices` performance and that it is crucial to consider both the type and the visibility of the support. Esteem support is particularly effective when communicated in an explicit and direct manner but informational support appears more effective when communicated in a more subtle, indirect manner.